1999
DOI: 10.1046/j.1365-2672.1999.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced toxicity of expression, in Escherichia coli, of antipollutant antibody fragments and their use as sensitive diagnostic molecules

Abstract: Single-chain antibody fragments (scAb), specific for the chlorophenoxy acid herbicide mecoprop, have been expressed and purified from the bacterium Escherichia coli. Co-expression with the colE1-compatible, arabinose-inducible, skp expression vector pHELP1 prevented bacterial lysis and significantly increased both total and functional expression yield. The periplasmic protein, SKP, may have a role as a generic detoxification protein. Surface plasmon resonance (BIAcore 2000) analysis confirmed that the purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Co-expression of chaperone proteins such as the Skp chaperone protein with antibody fragments had been reported to reduce toxicity and to enhance the proper folding of scFv or Fab fragments expressed in E. coli (35), and Levy et al demonstrated that co-expression of Skp or DsbC chaperone protein increased the cytoplasmic production of functional Fab fragments up to 5-6-fold (23). Additionally, DsbC co-expression increases the yield of tissue plasminogen activator (tPA) in the cytoplasm of E. coli by more than 20-fold (36).…”
Section: Resultsmentioning
confidence: 99%
“…Co-expression of chaperone proteins such as the Skp chaperone protein with antibody fragments had been reported to reduce toxicity and to enhance the proper folding of scFv or Fab fragments expressed in E. coli (35), and Levy et al demonstrated that co-expression of Skp or DsbC chaperone protein increased the cytoplasmic production of functional Fab fragments up to 5-6-fold (23). Additionally, DsbC co-expression increases the yield of tissue plasminogen activator (tPA) in the cytoplasm of E. coli by more than 20-fold (36).…”
Section: Resultsmentioning
confidence: 99%
“…Single E. coli XL‐1 Blue colonies containing antibodies specific for microcystin were grown overnight in 5 ml LB containing 1% (w/v) glucose, 50 μg ml −1 amp and 12.5 μg ml −1 tetracycline at 37°C using published methods[13]. Each culture was used to inoculate 50 ml Terrific broth (TB)–glu–amp–tet in 250‐ml baffled flasks and the culture grown to an OD of 15.…”
Section: Methodsmentioning
confidence: 99%
“…Single E. coli XL-1 Blue colonies containing antibodies speci¢c for microcystin were grown overnight in 5 ml LB containing 1% (w/v) glucose, 50 Wg ml 31 amp and 12.5 Wg ml 31 tetracycline at 37 ‡C using published methods [13]. Each culture was used to inoculate 50 ml Terri¢c broth (TB)^glu^amp^tet in 250-ml ba¥ed £asks and the culture grown to an OD of 15.…”
Section: Large Scale Expression and Puri¢cation Of Anti-hapten Antibomentioning
confidence: 99%
“…Two immunotubes were coated overnight with 100 Wg ml 31 microcystin LR^BSA in phosphate bu¡ered saline (PBS), washed with PBS and blocked with 2% skimmed milk^PBS at room temperature for 2 h. The concentrated phage particles (approximately 1U10 13 ) from each library (Gri⁄n or Tomlinson) were added to the immunotubes. Speci¢c scFv phage bound to the antigen, and the unbound phage were removed by washing.…”
Section: A⁄nity Selection Of Anti-microcystin Lr Phage Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation